2007
DOI: 10.1167/iovs.06-1139
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Glaucoma Using Scanning Laser Polarimetry with Enhanced Corneal Compensation

Abstract: GDx ECC performed significantly better than VCC for diagnosing glaucoma in patients with more severe atypical patterns of retardation and at earlier stages of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 19 publications
(21 reference statements)
5
76
2
4
Order By: Relevance
“…We have recently demonstrated how a control cohort with no suspicious findings of glaucoma can affect the diagnostic ability of SDOCT parameters in glaucoma compared with a control cohort which is likely to be misinterpreted as glaucoma. 16 Due to the same reason, AUCs of RNFL parameters reported in our study are also lower compared with the studies that have reported the same with SDOCT 7,10,29 and GDx ECC 5,12,13,30 separately.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…We have recently demonstrated how a control cohort with no suspicious findings of glaucoma can affect the diagnostic ability of SDOCT parameters in glaucoma compared with a control cohort which is likely to be misinterpreted as glaucoma. 16 Due to the same reason, AUCs of RNFL parameters reported in our study are also lower compared with the studies that have reported the same with SDOCT 7,10,29 and GDx ECC 5,12,13,30 separately.…”
Section: Discussioncontrasting
confidence: 44%
“…The general principles of SLP and the algorithm used for ECC have been described in detail previously. 3,5,12 The parameters generated on the printout and used in this study were temporal average (temporal 50 degree), superior average (superior 120 degree), nasal average (nasal 70 degree), inferior average (inferior 120 degree), TSNIT (temporal superior nasal inferior and temporal) average (over 360 degree), TSNIT SD, and nerve fiber indicator (NFI). TSNIT SD represents the SD of the values contained in the calculation circle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 The introduction of a variable corneal polarization compensator (GDxVCC) attempted to alleviate this problem and resulted in improved diagnostic accuracy. 54 The GDxVCC scans, however, were found to be limited by atypical retardation patterns (ARPs). ARPs result from poor noise-to-signal ratio as a consequence of light scattering in the eye.…”
Section: Cslomentioning
confidence: 99%
“…Numerous studies [17][18][19][20][21][22][23][24] have reported the sensitivity and specificity of different versions of SLP for discriminating between healthy and glaucomatous eyes. Very few studies [25][26][27][28] however have tried to combine SLP variables to obtain an LDF to increase the diagnostic accuracy of isolated GDx-VCC-provided parameters.…”
Section: Discussionmentioning
confidence: 99%